Social Media and Higher Education – An International Perspective - Małgorzata Bartosik-Purgat; Nela Filimon; Meltem Kiygi-Calli (Economics & Sociology)
This study explores the use of social media in higher education with a particular focus on the role of cultural and socioeconomic differences. The dataset, built on surveyed respondents from China, Poland, Spain, Turkey and United States, was analysed using quantitative techniques that allowed us to test various hypotheses. Findings show that the use of social media for educational purposes is determined by socio-demographic variables (gender, age, education level) that returned different social media users’ profiles across countries. Overall, the results indicate that social media is a useful tool of communication between teachers and students but that national cultural differences must be taken into account in the design of subjects and teaching materials used by teachers in the digital environment. From another point of view, the results related with the cultural differences and the socio-economic determinants may give insight to the marketers in the promotion of education related products such as books, language schools, degree and certificate programs in social media.